Pengaruh Financial Distress, Sales Growth dan Umur Perusahaan Terhadap Tax Avoidance pada Perusahaan Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022 - Gurusinga, Latersia Br; Hidayat, Ferry; Lobion, Sellina (BUDGETING : Journal of Business, Management and Accounting, 2024)
Tax avoidance is the exploitation of weaknesses or gray areas in tax regulations by companies with the aim of reducing the amount of tax payable. This research was conducted to examine and analyze the influence of financial distress, sales growth, and company age on tax avoidance in basic and chemical industry companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. This study used secondary data and resulted in 126 samples for analysis. The results of this study indicate that, partially, the variables of financial distress and sales growth do not affect tax avoidance. However, the variable of company age has a positive effect on tax avoidance. Simultaneously, financial distress, sales growth, and company age have a positive effect on tax avoidance. Keywords: , Company Age, Financial Distress, Sales Growth, Tax Avoidance.